Progesterone restores the female prostate activity in ovariectomized gerbil and may act as competitor of testosterone in intraprostatic environment - Shinohara, Filipe Z.; Silva, Diego A.L.; Zanatelli, Marianna; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Santos, Fernanda C.A.; Taboga, Sebastião R. [UNESP] (Elsevier, 2013)
Aims Little is known about the effect of progesterone on gerbil female prostate. It is known that normal oscillation in the progesterone and estradiol levels during the estrous cycle phases influence the morphophysiology of this gland. The present study aims to evaluate the isolated effect of prolonged administration of progesterone combined or not with testosterone on the prostate of ovariectomized female gerbil. Main methods To observe the morphological changes caused by castration in the prostate of different groups stereologic analyses of all prostate compartments, analysis of nuclear area and perimeter, and morphometric measurements of epithelial and smooth muscle cells layers were used. In addition, immunocytochemistry was performed to investigate the distribution of the androgen, estrogen alfa and beta and progesterone receptors in different prostatic compartments. Key findings This study demonstrated that both treatments partially recovered the structure of the gland. In the group treated with progesterone plus testosterone a higher incidence of epithelial and stromal disorders occurred, besides the absence of secretory activity. Thus, treatment only with progesterone showed better results in the restoration of glandular homeostasis mainly seen by the regulation of the secretory activity. Significance Collectively, the findings of this study indicate that progesterone may have a significant role on the maintenance of prostate morphophysiology, and showed an interesting evidence of hormonal competition between progesterone and testosterone. © 2013 Elsevier Inc.
Keywords: Female prostate; Progesterone; Prostate; Testosterone; androgen; estrogen; progesterone; testosterone; castration; epithelium cell; female; gerbil; immunocytochemistry; morphometrics; nonhuman; ovariectomy; perimeter; prostate; secretion (process); smooth muscle fiber; stereology; Animals; Estradiol; Female; Genitalia, Female; Gerbillinae; Immunohistochemistry; Ovariectomy; Receptors, Androgen; Receptors, Estrogen; Receptors, Progesterone